Analysis of evidence in forensic medicine. Validation of the test method as a tool to control parameters determining the reliability of the analysis results - Szczęśniak, Angelika; Serwin, Natalia; Cecerska-Heryć, Elżbieta; Stangret, Anna; Mularczyk, Agata; Grzeszczak, Konrad; Topczewska, Katarzyna (Journal of Education, Health and Sport, 2020)
Currently, forensic research foundation is comprised of the methods of genetic analysis. The study of DNA polymorphism became a source of highly reliable evidence, which allow the determination of the genetic profile of biological traces containing genetic material of barely a few cells, collected from all possible substrates, and their further comparison with the genetic profile of the victim or suspect. The forensic expertise of such research, supported by relevant statistical calculations is one of the few objective evidence in criminal proceedings. The process of DNA testing for forensic purposes is composed of several stages and a number of analyzes. After securing suitable test specimen, the isolation of genetic material is performed. For the quantitative and qualitative analysis of the isolate, the Real Time PCR reaction is performed. This is a crucial moment for the study because it is the assessment of the suitability of samples for further testing. The next step is the amplification of DNA fragments with Multiplex PCR technique. Then, as a result of electrophoretic separation of the sequencer we obtain a genetic profile. Thus obtained profiling results are interpreted as well as compared by specialists. For analysts in the field of forensic medicine it is necessary to obtain clear genetic profiles. Given the often small amount of DNA that can be obtained and the need for unquestionability of the evidence, it is very important to develop a method with high sensitivity, which allows to obtain completely reliable results. In order to ensure the quality of the research, forensic laboratories must apply the standards and guidelines set by international associations, periodically calibrate their testing equipment, keep complete records of the results and, above all, to validate the used methods. In the laboratory, which intends to apply the procedure in question, internal validation must be carried out. The aim of this process is to determine the reliability and limitations of the method. During the test, the results of manufacturers’ verification are validated and the level of efficiency of the said procedure within a particular lab is checked.